ISOLATED OCULOMOTOR NERVE PALSY - Ratag, Melissa T. E.; Pangalila, Ralf R (Jurnal Biomedik : JBM, 2013)
Abstract: We reported a case of a 59-year-old male who came to the hospital with the chief complaint of a droopy upper right eyelid originating a month before, accompanied by diplopia. This patient was also suffering from uncontrolled hypertension. The ophthalmologic examination of the right eye showed a best corrected visual acuity (BCVA) of 1.0. In the primary position there was a deviation to the temporal side; limitations on elevation, adduction, and depression; and an endorotation on nasal down gaze. The aberrant regenerative trigeminal nerve was noticed, but the relative afferent pupillary defect (RAPD) was not found. The anterior and posterior segments of the right eye were normal. Laboratory tests were within normal limits and the CT-scan did not show any abnormality. Conclusion: Based on all the tests performed, the diagnosis of the patient was an isolated oculomotor nerve palsy of the right eye. The patient was treated with a non-steroid anti inflammatory drug and a neurotropic vitamine, and had to be observed for three months. Keywords: palsy, oculomotor nerve, right eye.Â Â  Abstrak: Kami melaporkan kasus seorang laki-laki berusia 59 tahun dengan keluhan utama kelopak mata atas kanan tertutup sejak satu bulan lalu, disertai diplopia. Dalam anamnesis ditemukan adanya riwayat hipertensi sedangkan riwayat trauma tidak ada. Pemeriksaan oftalmologi mata kanan didapatkan tajam penglihatan 6/6, pergerakan bola mata kanan tampak sedikit deviasi ke temporal pada posisi primer, serta keterbatasan dalam elevasi, aduksi, dan depresi. Mata kanan tampak endorotasi saat melirik ke nasal bawah dan terdapat aberrant regenerative; relative afferent pupillary defect (RAPD) tidak ditemukan. Segmen anterior dan posterior dalam batas normal. Pemeriksaan laboratorium dan CT scan kepala dalam batas normal. Simpulan: Berdasarkan hasil pemeriksaan oftalmologik dan pemeriksaan penunjang ditegakkan diagnosis isolated oculomotor nerve palsy mata kanan yang ditangani dengan pemberian anti inflamasi non steroid dan neurotropik per oral sambil diobservasi selama tiga bulan. Kata kunci: kelumpuhan, saraf okulomotor, mata kanan.